« Le fauteuil d’amour » du prince de Galles : la légende à l’épreuve des archives - Michèle Mariez (Les Cahiers de l'École du Louvre)
Throughout the second half of the nineteenth century and the first half of the twentieth century, Maison Soubrier (1818–) supplied quality furniture to a wealthy, privileged clientele, both French and foreign, including private individuals, institutions and private companies. In the world of eroticism, it is best known for having produced a “love seat” for the Prince of Wales, the future Edward VII, around 1900, a special commission from Chabanais, the most popular brothel in Paris. A study of the Soubrier archives donated to the library of the Musée des Arts Décoratifs in 2017 by the current descendants of the house has yielded previously unpublished information that sheds light on the history of this exceptional piece of furniture.